Endoplasmic reticulum stress may activate NLRP3 inflammasomes via TXNIP in preeclampsia - Yang, Yong; Li, Jianxin; Han, Ting-Li; Zhou, Xianbo; Qi, Hongbo; Baker, Philip N.; Zhou, Wei; Zhang, Hua (Cell and tissue research, 2020)
Preeclampsia (PE) development is often associated with placental immune and inflammatory dysregulation, as well as endoplasmic reticulum (ER) stress. However, the mechanisms linking ER stress and inflammatory dysregulation to PE have not been elucidated. It has been reported that thioredoxin-interacting protein (TXNIP), which can bind with and activate the NLR family pyrin domain containing 3 (NLRP3) inflammasome, is a key point in immune regulation. Recent experimental evidence suggests that activated NLRP3 inflammasomes can activate interleukin-1β (IL-1β) production in the placenta of patients with PE. The objective of the current study was to explore if TXNIP plays a critical signaling role linking ER stress with NLRP3 inflammasome activation in PE. We hypothesized that ER stress would induce TXNIP production, which would bind with NLRP3 inflammasomes to activate IL-1β production. These cells showed a higher protein level of NLRP3 and IL-1β, as well as a higher enzymatic activity of caspase-1, indicating enhanced inflammatory dysregulation and ER stress. Cells transfected with TXNIP siRNA showed reduced NLRP3 inflammasome activation. Cells treated with 4-phenylbutyric acid, an inhibitor of ER stress, showed a similar result. Outgrowth of the explant with TXNIP lentivirus in H/R or tunicamycin (inducers of ER stress) was also measured to verify our hypothesis. These findings demonstrated that TXNIP could influence inflammatory dysregulation by mediating ER stress and NLRP3 inflammasome activation in PE. This novel mechanism may further explain the inflammation observed at the maternal-fetal interface, which leads to placental dysfunction in a patient with PE.